Pemanfaatan Wordwall dalam Asesmen Diagnostik Kognitif di SMP Negeri 34 Semarang - Sab’ah Ashfiya Adiratna Salim Putri; Asep Purwo Yudi Utomo; Martina Puspita Rakhmi; Wildan Ghufron; Amilia Buana Dewi Islamy; Annisa Tetty Maharani; Monica Chandra Ayuningsih (Lembaga Pengembangan Kinerja Dosen, 2024)
In the industrial era 4.0 which stands out for its technology, learning activities must also use learning innovations. One of these learning activities is a cognitive diagnostic assessment. The assessment aims to identify the basic abilities, strengths, and abilities of students. In learning the new paradigm, diagnostic assessment has an important role, one of which is as material for designing future learning. This study aims to describe the use of the Wordwall website-based application used for cognitive diagnostic assessment. The research method used in this research is descriptive qualitative. The data in the study were obtained from questionnaires distributed to students randomly. The data source is class VII students of SMP Negeri 34 Semarang. In this study it was shown the results of his research, namely the use of Wordwall was able to represent the abilities of students with a percentage of 75.8%. In addition, the use of Wordwall is able to give a pleasant impression to students with a percentage of 100%. All respondents also responded that the use of Wordwall was able to attract students' interest in learning the material to be studied. ‎